Architecture and Politics in Africa Making, living and imagining identities through buildings - Tomkinson, Joanne; Mulugeta, Daniel; Gallagher, Julia; Yekoyesew, Dawit; Ofori-Sarpong, Emmanuel K. (Making & Remaking the African City: Studies in Urban Africa, 2022)
Buildings shape politics in the ways they define communities, enable economic activity, reflect political ideas, and impact state-society relations. They are materially and symbolically interwoven with the everyday lives of elites and citizens, as well global flows of money, goods, and contracts. Yet, to date, there has been no research that explicitly connects debates about Africa's domestic and international politics with the study of architecture. This innovative book fills this gap, providing a new and compelling reading of the politics of identity in sub-Saharan Africa through an examination of some of its most significant buildings. Using case studies from nine countries across sub-Saharan Africa, this volume reveals how they are commissioned and built, how they enable elites to project power, and how they form a basis for popular conceptions of the state. Exploring a diverse range of buildings including parliaments, airports, prisons, ministries, regional institutions, libraries, universities, shopping malls, public housing, cathedrals and palaces, the contributors suggest a innovative perspective on African politics, identity and urban development. This book will be a compelling reference for scholars and students of African politics, development studies and city life in its elaboration of and challenges to established concepts and arguments about the relationship between material objects and political ideas. This book is available as Open Access under the Creative Commons license CC-BY-NC-ND.